2009
DOI: 10.3109/03091900903271646
|View full text |Cite
|
Sign up to set email alerts
|

An effective method for skin blood flow measurement using local heat combined with electrical stimulation

Abstract: Electrical stimulation (ES) is a modality used to increase skin blood flow (SBF) and to aid in wound healing. A greater SBF in non wounded skin is induced if ES is used in a warm environment compared to a thermoneutral environment, where ES is usually applied. Therefore, in this paper, a method to investigate the effect of local heating and ES on the SBF is developed. A total of 33 males (18-40 years) were divided into group G (n = 15) who received the ES during a global heating protocol and group L (n = 18) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…It is well established that skin blood flow increases to protect the skin after the application of local heat [1,3,14]. Pennes, in a classic paper, in modeling heat flow through tissue, showed that for a constant heat load applied to the skin, it is blood flow that is the most important contributor to removing heat [1,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that skin blood flow increases to protect the skin after the application of local heat [1,3,14]. Pennes, in a classic paper, in modeling heat flow through tissue, showed that for a constant heat load applied to the skin, it is blood flow that is the most important contributor to removing heat [1,14].…”
Section: Discussionmentioning
confidence: 99%
“…While the circulation cannot respond fast enough to protect the skin from a rapidly applied high heat source, the increase in circulation of the skin in response to a warm, sustained, locally applied heat source is a dual response. In the initial phase (first 3 min), tactile sensors in the skin cause an initial vasodilatation mediated by substance P and other vasoactive neuropeptides released from sensory nerves [3][4][5]. As this initial response subsides, there is a more prolonged increase in skin blood flow due to activation of endothelial nitric oxide synthetase by calcium released through TRPV4 voltage gated, temperature sensitive calcium channels [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, if the skin is cool, vasoconstriction predominates. If two electrodes are applied to the skin and stimulation is increased with square wave stimulation at a current of 20 milliamps and 40 pulses per second, the blood fl ow to the skin, as measured by laser Doppler imagers, does not change [ 1,100,121,122 ] . However, if the skin or the room is warmed fi rst to release the sympathetic vasoconstriction, then blood fl ow increases substantially during electrical stimulation of the skin and in the skin around wounds [ 1,100,121,122 ] .…”
Section: Skin Moisture Heat and Skin Blood Flowmentioning
confidence: 99%
“…[71][72][73] This protects the skin from rapid changes in temperature that might cause damage. [74][75][76] These neuropeptides are released when TRPV-1 voltage-gated calcium channels in skin tactile sensory receptors become active. 77,78 The release of neuropeptides then causes relaxation of vascular smooth muscle.…”
Section: The Mechanism Of Thermoregulationmentioning
confidence: 99%